1998
DOI: 10.1542/peds.101.1.61
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a High-protein, Low-fat, Ketogenic Diet on Adolescents With Morbid Obesity: Body Composition, Blood Chemistries, and Sleep Abnormalities

Abstract: The K diet can be used effectively for rapid weight loss in adolescents with morbid obesity. Loss in lean body mass is blunted, blood chemistries remain normal, and sleep abnormalities significantly decrease with weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 30 publications
4
80
2
1
Order By: Relevance
“…This shift to ketogenesis may play a direct role in the cytoprotective effects of IF, because it has been reported that rats fed a ketogenic diet exhibit increased resistance to seizures (25), and that ␤-hydroxybutyrate protects neurons in rodent models of Alzheimer's and Parkinson's diseases (27). Ketogenic diets are prescribed for some patients with epilepsy (26) and are also implemented in several popular weight-loss programs (40,41). The findings of this study suggest that IF can enhance health and cellular resistance to disease even if the fasting period is followed by a period of overeating such that overall caloric intake is not decreased.…”
Section: Resultsmentioning
confidence: 99%
“…This shift to ketogenesis may play a direct role in the cytoprotective effects of IF, because it has been reported that rats fed a ketogenic diet exhibit increased resistance to seizures (25), and that ␤-hydroxybutyrate protects neurons in rodent models of Alzheimer's and Parkinson's diseases (27). Ketogenic diets are prescribed for some patients with epilepsy (26) and are also implemented in several popular weight-loss programs (40,41). The findings of this study suggest that IF can enhance health and cellular resistance to disease even if the fasting period is followed by a period of overeating such that overall caloric intake is not decreased.…”
Section: Resultsmentioning
confidence: 99%
“…So far, very few reports are available dealing with adolescents who are affected with very severe forms of obesity and who underwent therapeutic regimen, which are beyond dietetic/ behavioural treatment programmes: drugs like sibutramin have been used, 1 as well as ketogenic diets 2 and very low calorie diets; 3 however, only short-term results in regard to weight loss have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown (17) that this diet induces rapid weight loss and improves sleep apnea while preserving lean body mass in nondiabetic obese children. In obese adults with type 2 diabetes, the diet has been shown to safely induce rapid weight loss while decreasing hyperinsulinemia (18) and improving blood pressure (19,20).…”
mentioning
confidence: 99%